The crossroads of gastroenterology and psychiatry – what benefits can psychiatry provide for the treatment of patients suffering from gastrointestinal symptoms - Sobański, Jerzy A.; Klasa, Katarzyna; Mielimąka, Michał; Rutkowski, Krzysztof; Dembińska, Edyta; Müldner-Nieckowski, Łukasz; Cyranka, Katarzyna; Smiatek-Mazgaj, Bogna; Popiołek, Lech (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction: Gastrointestinal symptoms are very common in the general population. Many of them coincide with mental disorders (especially with neuroses, stress-related disorders, somatisation disorders, autonomic dysfunction, and anxiety) that are associated with psychological trauma, conflicts, and difficulties with interpersonal relationships. Aim : Assessment of the association between gastrointestinal complaints and stressful situations in relationships, among patients admitted to day hospital for neurotic and behavioural disorders. Material and methods : Analysis of the likelihood of co-occurrence of abdominal symptoms and stressful situations, reported by patients before admission, in a large group of subjects treated with psychotherapy. Results : Gastrointestinal symptoms were highly prevalent in the studied group (they were reported by 40–50% of patients). The most common complaints in women were: loss of appetite (52%), nausea (49%), and constipation and flatulence (45%). In men the most prevalent symptoms were: loss of appetite (47%), heartburn (44%), and flatulence (43%). Functional gastrointestinal symptoms (especially vomiting in cases of nervousness in females or heartburn in males) were significantly associated with greater likelihood of current difficulties in interpersonal relationships, such as conflicts with partner/spouse or parent. Conclusions : The results suggest that in many cases symptoms of anxiety disorders or somatisation disorders coexisted with irritable bowel syndrome and functional dyspepsia.